Analysis of Procedures and Effectiveness of Covid-19 Cash Transfer Program (Case Study in Karangsari Village, Kulon Progo) - Wulaningrum, Puspita Dewi; Asrianto, Rizal (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
This study aims to determine the procedure and effectiveness of the distribution of the Village Fund Cash Transfer program in Karangsari Village, Subdistrict Pengasih, Kulon Progo Regency. The method used in this study is qualitative method. The type of data used is secondary data obtained from the realization report of the 2021 cash transfer program distribution and primary data obtained from interviews with informants. Data collection techniques are carried out using documentation and interview methods. The results of the study show that the effectiveness of cash transfer distribution in terms of timeliness, target accuracy, and budget accuracy has been running effectively. This can be seen from the qualitative data analysis of the statements expressed by informants in line with quantitative data calculations from the cash transfer distribution realization report which shows 100% figures from all aspects. Likewise, the procedures applied to the distribution process have been running in accordance with the regulations set by the government.